Digital Imaging - Sarfraz, Muhammad (IntechOpen, 2020)
Digital imaging is used widely in various real-life applications today. There are a number of potential digital imaging applications that include different areas such as television, photography, robotics, remote sensing, medical diagnosis, reconnaissance, architectural and engineering design, art, crime prevention, geographical information systems, communication, intellectual property, retail catalogs, nudity detection, face finding, industrial, and others. This book is specifically dedicated to digital imaging research, applications, techniques, tools, and algorithms that originate from different fields such as image processing, computer vision, pattern recognition, signal processing, artificial intelligence, intelligent systems, and soft computing. In general, this comprehensive book contains state-of-the-art chapters focusing on the latest developments using theories, methods, approaches, algorithms, analyses, display of images, visual information, and videos.